2017
DOI: 10.1111/phn.12324
|View full text |Cite
|
Sign up to set email alerts
|

Transitional care interventions: Relevance for nursing in the community

Abstract: Effective transitional care requires excellent communication between acute and primary care providers. This has implications for integration and organization of care across settings and nursing competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 27 publications
(154 reference statements)
0
28
0
6
Order By: Relevance
“…Previous research on patient involvement in transitional care has revealed that older patients experience a lack of participation during transitions [8][9][10][11]. Transitional care is also characterized by the challenges of coordinating care across organizational and disciplinary boundaries, managing conflicting goals of care, which may be stressful for health care providers (HCPs) [12][13][14]. Dyrstad et al [8] found that the focus on efficiency and time constraints affected patient involvement negatively, and practices were often task-oriented instead of patientoriented.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on patient involvement in transitional care has revealed that older patients experience a lack of participation during transitions [8][9][10][11]. Transitional care is also characterized by the challenges of coordinating care across organizational and disciplinary boundaries, managing conflicting goals of care, which may be stressful for health care providers (HCPs) [12][13][14]. Dyrstad et al [8] found that the focus on efficiency and time constraints affected patient involvement negatively, and practices were often task-oriented instead of patientoriented.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, quality of life of all patients who had received transitional care was higher than patients who had experienced other forms of care. In fact, it can be said that the transitional care model is a set of services and treatments that is complementary to primary care (1,17,18). This care model aims to ensure continuity of care and prevention of negative outcomes of patients at risk during the transition from hospital to home and it is among medical staff and caregivers.…”
Section: Literature Review In Transitional Care Modelmentioning
confidence: 99%
“…Transitional care is provided by expert nurses as complementary and supportive care in the patient's home and after discharge from the hospital. In this model, providing patient care is done through coordination between professional and skilled nurse with the patient and his family, doctors and other health care team members (2,4,16,17).…”
Section: Literature Review In Transitional Care Modelmentioning
confidence: 99%
“…This integration should operate within a primary care system, and through effective communications between specialist and primary care providers, to guarantee better transitions of care for patients with chronic disease. The latter has significant positive effects in reducing hospital readmissions and mortality 41–43 ( table 1G ).…”
Section: Methodsmentioning
confidence: 99%